Pemanfaatan Media Sosial Disparbud dalam Promosi Destinasi Wisata Kabupaten Majalengka - Karina Putri Hanifah; Suwandi Sumartias; Retasari Dewi (Unitri Press, 2022)
The Department of Tourism and culture of Majalengka Regency uses social media as one of the strategies to increase tourist visits in Majalengka Regency. This study aims to determine how the tactics paid media, earned media, shared media and owned media used Disparbud Majalengka to promote tourist destinations on social media.. The method used in this study is qualitative descriptive. Focus describes the stages of PESO tactics (Paid Media, Earned Media, Shared Media, and Owned Media) from the concept of ROSTIR Regina Luttrell. Data were collected from interviews, observations and literature studies. Data validity techniques using source triangulation. The results showed that, 1) Disparbud Majalengka has not done Media paid tactics due to cost constraints budgeted by the government; 2) Disparbud Majalengka using earned media tactics although not fully done by Disparbud Majalengka; Instagram Facebook 3) Disparbud Majalengka often shares, creates and promotes content created by the team as well as from followers; 4) Disparbud Majalengka owns and maintains official social media among Instagram, Facebook, Youtube and Twitter. Abstrak Dinas Pariwisata dan Kebudayaan Kabupaten Majalengka menggunakan media sosial sebagai salah satu strategi untuk meningkatkan kunjungan wisata di Kabupaten Majalengka. Penelitian ini bertujuan untuk mengetahui bagaimana taktik paid media, earned media, shared media dan owned media yang digunakan Disparbud Majalengka untuk mempromosikan destinasi wisata di media sosial. Metode yang digunakan dalam penelitian ini adalah kualitatif deskriptif. Fokus menjabarkan tahapan taktik PESO (Paid Media, Earned Media, Shared Media, dan Owned Media) dari Konsep ROSTIR Regina Luttrell. Data dikumpulkan dari hasil wawancara, observasi dan studi pustaka. Teknik validitas data menggunakan triangulasi sumber. Hasil penelitian menunjukan bahwa, 1) Disparbud Majalengka belum melakukan taktik paid media dikarenakan kendala biaya yang dianggarkan pemerintah; 2) Disparbud Majalengka menggunakan taktik earned media walaupun tidak sepenuhnya dilakukan oleh Disparbud Majalengka; 3) Disparbud Majalengka kerap membagikan, membuat dan mempromosikan konten yang dibuat tim maupun dari pengikut; 4) Disparbud Majalengka memiliki dan mengelola media sosial resmi diantara Instagram, Facebook, Youtube dan Twitter.